Complements or Substitutes? Immigrant and Native Task Specialization in Spain - Catalina Amuedo-Dorantes; Sara de la Rica (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2008)
Learning about the impact that immigration has on the labor market of the receiving nation is a topic of major concern, particularly in Spain, where immigration has more than doubled from 4 percent to roughly 10 percent of the population within a decade. Yet, very little is known about the impact that large immigrant inflows have had on the labor market outcomes of Spanish natives. Furthermore, most studies assume that natives and immigrants are perfect substitutes within skill groups -a questionable assumption given recent findings in the literature. In this paper, we first document that foreign-born workers are not perfect substitutes of similarly skilled native Spanish workers, which may help explain why immigration has not significantly lowered natives' wages. Instead, immigration has affected the occupational distribution of natives. Specifically, owing to the comparative advantage of foreign-born workers in manual as opposed to interactive tasks, natives relocated to occupations with a lower content of manual tasks -such as technical and alike professional occupations, clerical support jobs, and sales and service occupations. Yet, possibly owing to the significant and simultaneous reduction in the manual to interactive task supply resulting from the increase in the share of native female workers, the increase in the relative supply of manual to interactive tasks from foreign-born workers does not appear to have significantly changed the overall manual to interactive task supply in the Spanish economy.
Keywords: 330